Efektivitas Media Aplikasi Quizizz dalam Pembelajaran Pendidikan Agama Islam pada Era Merdeka Belajar - Agus Fudholi; Haerudin; Jodi, Haerudin (Jurnal Sekolah Dasar, 2023)
The purpose of this study was to find out how effective the use of the Quizizz application is in learning Islamic religious education in the Free Learning Era. This study used descriptive qualitative method. As for the subjects in this study, namely teachers and students of SDN Kertamulya II class. The data collection technique used in this study used documentation, questionnaires, and interviews with the subject of teachers and grade V students. The results of research that had been carried out on the Effectiveness of Quizizz Application Media in PAI Learning in the independent era studied at SDN Kertamulya II. Based on the results of data analysis and discussion, it can be concluded that the results of the research above show the effectiveness of using the Quizizz application in PAI learning in the independent learning era, in terms of student response and achievement, which has been running effectively. This was obtained from the results of questionnaires and interviews which showed positive results regarding the use of the Quizizz application from various parties, both students and teachers. As well as having a big influence on students from using this application, for example students are getting more excited when working on questions with this application, and making students more serious in listening to the material conveyed by the teacher, and making students motivated. This is seen from the results of the presentation of the questionnaire given by the researcher.